Rekindling Union Democracy Through the Use of Sortition - Pek, Simon (Journal of business ethics, 2019)
There is a long-standing and growing interest in democratizing labor unions. Union democracy is important for many reasons, including fostering greater member voice in the workplace and society, improving the internal effectiveness of unions, building members’ capacities to engage in democracy in other contexts, and helping foster union renewal. Despite these benefits, democracy in unions as practiced today is characterized by several problems. In this paper, I analyze several of the remedies to increase union democracy proposed to date by scholars and practitioners, finding that despite their potential positive impacts, many of them may have inherent limitations. I then argue that sortition—the use of lotteries in selecting leaders—shows potential in helping address many of the problems facing union democracy and overcoming the limitations of recent remedies. An important democratic tool in Ancient Athens and other city-states, sortition has a long history in political theory and practice, yet application to unions is in its infancy. I conclude by developing and evaluating several ways in which sortition could be used as a tool in union governance structures, and by discussing the implications of my theorizing for ongoing work on union democracy and union renewal.